Public Policy and Petroleum Development: The Alaska Case - Thomas, Wayne C.; Thomas, Monica E. (ARCTIC, 1982)
Present and potential petroleum development in Alaska is directly related to public-policy issues. The Prudhoe Bay oil discovery signaled the need for determination of a transportation route to market. Pipeline location became a function of political boundaries, with an all-American route preferred. Actual pipeline construction was dependent on settlement of land claims with Alaska's indigenous peoples and the development of environmental safeguards. However, implicit in the U.S. Congressional decision to build the pipeline was acceptance that expanded human activity would impinge on northern Alaska's pristine wilderness and that there was probable risk of environmental damage. Another major public-policy decision was to allow construction of a pipeline for Prudhoe Bay natural gas. The problem that remains is uncertain economics; thus no Alaskan construction has occurred to date. Public policy also was advanced in windfall-profit taxation, and towards exploration and development of new petroleum areas. Each policy has generated conflict between state and federal governments and private groups, but overall public-policy decisions and related judicial actions continue to favor a development stance. This is likely to persist as long as U.S. national attention is drawn to the uncertainty of foreign sources for petroleum.Key words: Alaska, petroleum, public policy Mots clés: Alaska, pétrole, politique publique